Improving attitudes towards minority groups by thinking about the thoughts and meta-cognitions of their members - Martínez, Rocío; Briñol, Pablo; Petty, Richard; Santos, David (John Wiley and Sons Ltd, 2022)
Research on persuasion has shown that for attitudes to change people need to take into consideration not only the thoughts message recipients generate in response to proposals but also how people think about their own thoughts (metacognition). In the present research,we introduce a new perspective for improving outgroup attitudes focused on the distinction between cognition and metacognition but this time applied to the perceptions of others’ minds. Specifically,we examined to what extent thinking about the mental processes of outgroup members influences attitudes towards those outgroups. We compared the impact of thinking about how others think (perceived primary cognition) with how others think about their own thoughts (perceived secondary cognition or metacognition). In the primary cognition treatment,participants answered questions about the thinking processes of outgroup members. In the secondary cognition treatment,participants answered questions that required them to consider how outgroup members think about their own thoughts (i.e.,metacognition). Compared to controls,these treatments were capable of improving attitudes of Spanish citizens towards Syrian refugees,South American immigrants,and Roma people. A third study used a minimal group paradigm in which a fictitious outgroup was described as having primary (vs. secondary) cognition. A final study also tested the implications of assuming that groups have one type of cognition or another. The effects of the two treatments varied depending on the type of outgroup. © 2022 The Authors. European Journal of Social Psychology published by John Wiley & Sons Ltd.
Keywords: Adults; Cognition; Dehumanization; Female; Human; Human experiment; Immigrant; Male; Mental function; Metacognition; Minority group; Perception; Prejudice; Refugee; Romani (people); Spaniard; Attitudes; Dehumanization; Metacognitive interventions; Minorities outgroups; Prejudice reduction; ODS 10 - Reducción de las desigualdades